2020
DOI: 10.1039/d0cp01634a
|View full text |Cite
|
Sign up to set email alerts
|

On-surface synthesis of extended linear graphyne molecular wires by protecting the alkynyl group

Abstract: In this paper we report on the use of an Ullmann-like aryl halide homocoupling reaction to obtain long Graphyne Molecular Wires (GY MWs) organized in dense, ordered arrays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…It has been reported that degradation processes often occur heterogeneously, for example, proceeding more rapidly at solid–liquid interfaces than in bulk. Thus, obtaining a clear picture of the spatial variation of the interfacial degradation processes at the molecular level is very important. On-surface decomposition of organic layers can serve as a model for obtaining nanoscale mechanistic insights into material degradation processes. Spatially resolved investigation of the decomposed sites and reactive intermediates involved at interfaces is crucial to the clear elucidation of the degradation mechanism. To achieve this, both high spatial resolution and chemical selectivity are required for characterization, which conventional analytical techniques used to study on-surface degradation chemistry often do not provide.…”
mentioning
confidence: 99%
“…It has been reported that degradation processes often occur heterogeneously, for example, proceeding more rapidly at solid–liquid interfaces than in bulk. Thus, obtaining a clear picture of the spatial variation of the interfacial degradation processes at the molecular level is very important. On-surface decomposition of organic layers can serve as a model for obtaining nanoscale mechanistic insights into material degradation processes. Spatially resolved investigation of the decomposed sites and reactive intermediates involved at interfaces is crucial to the clear elucidation of the degradation mechanism. To achieve this, both high spatial resolution and chemical selectivity are required for characterization, which conventional analytical techniques used to study on-surface degradation chemistry often do not provide.…”
mentioning
confidence: 99%
“…Concerning the type-2 chains, they are partially cross-linked and are about 8–24 nm long and 1–3 nm wide, in line with typical sizes for covalent polymerization of similar systems based on small aromatic precursors. 36,41–44 The presence of 1D extended chains testifies that both active sites designed for covalent coupling are activated at this temperature, together with possible co-operating metal–organic bonds. Nevertheless, due to their intricate and stochastic structure, the chain analysis does not allow a clear assignment of precursor evolution upon coupling.…”
Section: Resultsmentioning
confidence: 97%
“…The reaction intermediates and products were unambiguously uncovered by STM, and reaction pathway was comprehended with the aid of DFT calculations. Instead of using terminal alkyne or forming C-C triple bond, another simple avenue to generate graphyne nanowire is the Ullmann coupling of precursor bearing internal alkynyl, as reported by Sedona et al [152]. The formation of well-defined graphyne chain was proposed to result from registry of OM and covalent chain with substrate, as well as Br adatoms acting as separator.…”
Section: Graphyne Chainsmentioning
confidence: 99%